Aperiodic quantum oscillations of particle-hole asymmetric Dirac cones. (29th November 2017) - Tisserond, E.; Fuchs, J. N.; Goerbig, M. O.; Auban-Senzier, P.; Mézière, C.; Batail, P.; Kawasugi, Y.; Suda, M.; Yamamoto, H. M.; Kato, R.; Tajima, N.; Monteverde, M.
Abstract: We report experimental measurements and theoretical analysis of Shubnikov-de Haas (SdH) oscillations in a Dirac cone system: the α -(BEDT-TTF)2 I3 organic metal under hydrostatic pressure. The measured SdH oscillations reveal anomalies at high magnetic fields B where the 1/ B oscillations periodicity is lost above 7 T. We interpret these unusual results within a theoretical model that takes into account intrinsic distortions of the α -(BEDT-TTF)2 I3 Dirac cones such as a parabolic particle-hole asymmetric correction. Others possible causes, such as a cone tilting or a Zeeman effect, are carefully ruled out. The observations are consistent among α -(BEDT-TTF)2 I3 samples with different Fermi levels.